TINGKAT KESEJAHTERAAN RUMAH TANGGA PEKERJA BATU BATA DI KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI - Dilla Atika; Fitriana Syahar (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to 1) determine the level of household welfare of brick industry worker in Mandiangin Koto Selayan sub district. 2) knowing the distribution pattern of the brick industry in the Mandiangin Koto Selayan sub district Bukittinggi city.This research is a type of quantitative descriptive research. The population in this study are brick worker. The analysis technique is the percentage and nearest neighbor analysis using ArcGis 10.2 software. Research result 1) the level of household welfare of brick craftsmen in Mandiangin Koto Selayan district which occupies the highest level is prosperous family 1 of 37,17% basen on BKKBN indicators. 2) Based on the results of the nearest neighbor analysis conducted at the brick industri location in the Mandiangin Koto Selayan sub-district, it is included in the (cluster pattern)category with the nearest neighbor index value below 0 which is 0.0002 including the characteristics of the clustered distribution pattern.